THE ROLE OF HYPERHOMOCYSTEINEMIA IN THE DEVELOPMENT OF COGNITIVE IMPAIRMENT IN CHRONIC CEREBRAL ISCHEMIA - Xatamova Sarvinoz Muyitdinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Summary Increased  levels  of  C-reactive  protein  (CRP)  and  hypercomocysteinemia  are considered  as  independent  factors  for  the  development  of  endothelial  damage  and atherosclerosis. The sluggish inflammatory process that occurs in the endothelium is usually  not  associated  with  infections.  The  accumulation  of  homocysteine  leads  to loosening  of  the  walls  of  the  arteries,  the  appearance  of  local  defects  in  the endothelium. People with high homocysteine levels in this group have an increased risk of Alzheimer's disease and cognitive impairment.